The effect of culturally-integrated TEE model teaching materials on secondary school students’ critical thinking skills and cultural literacy competence - Sumardi, Lalu; Sawaludin,; Mustari, Mohamad; Sialana, Fatimah; Simaremare, Tohap Pandapotan; Saputri, Annisa (Frontiers in Education, 2026)
This study examines the effect of culturally integrated TEE model-based Pancasila and Civic Education teaching materials on students’ critical thinking and cultural literacy competence and explores differences in students’ critical thinking and cultural literacy based on gender. The field testing employed a quasi-experimental pretest–posttest design with total of 64 students participated in the study, with participants randomly and evenly distributed across the control and experimental groups. Data were collected through questionnaires and cultural literacy tests, and analyzed using MANOVA. Research findings are: (1) The culturally integrated TEE model-based Pancasila and Civic Education teaching materials had a statistically significant partial and simultaneous effect on students’ critical thinking skills and cultural literacy competence. (2) Male students demonstrated higher levels of critical thinking and cultural literacy than female students. In the experimental group, the N-gain score for critical thinking was 0.73 for female students and 0.77 for male students. In the control group, the N-gain score was 0.29 for female students and 0.33 for male students. For cultural literacy, the N-gain score in the experimental group was 0.69 for female students and 0.79 for male students, while in the control group it was 0.41 for female students and 0.42 for male students. These findings indicate that the culturally integrated TEE model-based Pancasila and Civic Education teaching materials effectively enhance students’ critical thinking skills and cultural literacy.